The Methods and Practices of the Anglican Church of Uganda for Environmental Promotion and Protection - Kimanje, Bbosa Esau (International journal of multicultural and multireligious understanding, 2024)
The study focuses on the methods and practices of the Anglican Church of Uganda for environmental promotion and protection. This research uses a qualitative approach with a literature study method. Primary sources enabled the study to generate firsthand information known as primary data. During the collection of data, the researcher used interviews, focus group discussions, and observation methods. Secondary data was collected through a major document review and analysis. From documents, the study generated secondary information that gave a broader perspective of the research questions and concepts for this study which was also cost-friendly. The results from the respondents confirmed that Christians are enabled to take their obligation seriously to promote and protect the environment. It was shown from the data obtained from the respondents that some of the Christians are regularly educated about environmental promotion and protection. The findings from the respondents suggested that the Anglican Theological Institutions of learning include environmental issues in their curricula. It was revealed by the respondents that a full week of reflection on stewardship of the environment annually was designated by the Anglican Christians of Uganda.